(untitled) (CSIAM Transactions on Applied Mathematics, 2023)
We study the (2+1)-dimensional continuum model for the evolution of stepped epitaxial surface under long-range elastic interaction proposed by Xu and Xiang (SIAM J. Appl. Math. 69 (2009), 1393–1414). The long-range interaction term and the two length scales in this model makes PDE analysis challenging. Moreover, unlike in the (1+1)-dimensional case, there is a nonconvexity contribution in the total energy in the (2+1)-dimensional case, and it is not easy to prove that the solution is always in the well-posed regime during the evolution. In this paper, we propose a modified (2+1)-dimensional continuum model based on the underlying physics. This modification fixes the problem of possible ill-posedness due to the nonconvexity of the energy functional. We prove the existence and uniqueness of both the static and dynamic solutions and derive a minimum energy scaling law for them. We show that the minimum energy surface profile is mainly attained by surfaces with step meandering instability. This is essentially different from the energy scaling law for the (1+1)-dimensional epitaxial surfaces under elastic effects attained by step bunching surface profiles. We also discuss the transition from the step bunching instability to the step meandering instability in (2+1)-dimensions.